1985
DOI: 10.1016/s0735-1097(85)80257-6
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine: Its potential for inducing ischemic left ventricular dysfunction

Abstract: As an agent potentially capable of inducing ischemia in patients with coronary artery disease, dopamine administered intravenously was evaluated as a pharmacologic stress agent by supine radionuclide angiography, and the results were compared with ergometer exercise. In a preliminary group of 11 subjects (4 normal subjects and 7 patients with coronary disease), dopamine alone was administered in increments of 2.5 micrograms/kg per min to a maximum of 15 micrograms/kg per min. There were significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To our knowledge, this is the first study to investigate the safety and hemodynamic effects of dopamine and atropine stress in ALD patients and the second study to investigate the use of dopamine as a stress agent. Wisenberg et al found peak heart rate, SBP and RPP were comparable between dopamine‐atropine stress and bicycle exercise suggesting the potential of dopamine stress to approximate the hemodynamic changes and degree of stress produced by exercise 9 . Our study was prompted after the realization that DSE yields a lower than desired sensitivity in patients with ALD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To our knowledge, this is the first study to investigate the safety and hemodynamic effects of dopamine and atropine stress in ALD patients and the second study to investigate the use of dopamine as a stress agent. Wisenberg et al found peak heart rate, SBP and RPP were comparable between dopamine‐atropine stress and bicycle exercise suggesting the potential of dopamine stress to approximate the hemodynamic changes and degree of stress produced by exercise 9 . Our study was prompted after the realization that DSE yields a lower than desired sensitivity in patients with ALD.…”
Section: Discussionmentioning
confidence: 97%
“…Wisenberg et al found peak heart rate, SBP and RPP were comparable between dopamine-atropine stress and bicycle exercise suggesting the potential of dopamine stress to approximate the hemodynamic changes and degree of stress produced by exercise. 9 Our study was prompted after the realization that DSE yields a lower than desired sensitivity in patients with ALD.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies ex amining the results of exercise tests during atropine treatment may be hampered by the small number of patients (less than 20) in volved in each. The effects of inhaled atropine or atropine derivatives or the effects of atro pine in combination with other drugs on exer cise parameters have been widely discussed [17,18]. However, results do not necessarily reflect the isolated cardiotropic effects of atro pine.…”
Section: Discussionmentioning
confidence: 99%